Spectroscopic differentiation between monomeric and aggregated forms of BODIPY dyes: effect of 1, 1-dichloroethane. Issue 73 (19th July 2016) - Castillo, Marlius; Raut, Sangram L.; Price, Sarah; Bora, Ilkay; Jameson, Laramie P.; Qiu, Changling; Schug, Kevin A.; Gryczynski, Zygmunt; Dzyuba, Sergei V.
Abstract : 1, 1-Dichloroethane (1, 1-DCE) can induce spectroscopic differentiation between aggregated and monomeric forms of BODIPY dyes. Abstract : 1, 1-Dichloroethane induces a monomer–aggregate equilibrium of common BODIPY dyes in organic solvents at low μM dye concentrations, thus providing an opportunity to study monomeric, aggregate-free forms of BODIPY dyes.